Eco-Innovation in The Peruvian Amazon: Perspectives and Initiatives for A Resilient Future - Salazar, Carlos Alberto Hinojosa; Escobar, Benjamín Roldan Polo; Paco , Edwin Gonzales; Zubiate, Franz Tito Coronel; Giribaldi, Ana Myriam Ramos; Benavides, Anita Maribel Valladolid (Journal of Ecohumanism, 2024)
The Peruvian Amazon is emerging as a hotspot of innovation and sustainability, driving transformational change that transcends geographic boundaries and attracts global attention. In this dynamic and promising context, this article explores the impact of innovation and sustainable development in the Peruvian Amazon region, highlighting its importance in global competitiveness and its potential to lead a resilient and prosperous future. The objective was to analyze the prospects and initiatives for innovation and sustainable development in the Peruvian Amazon region. In particular, it seeks to delve into how these initiatives could catalyze a transformation in the Amazon, strengthening its competitiveness in the global scenario. This study applied a qualitative-descriptive methodology, using surveys and data analysis with SPSS. This methodological choice was based on the need to obtain an exhaustive understanding of the subject, allowing the exploration of both the perceptions and experiences of the participants and the associated numerical data. The sample population consisted of 75 stakeholders. In conclusion, our study represents a significant contribution to the field by addressing a gap in existing knowledge on innovation and sustainable development in the Peruvian Amazon. By presenting new perspectives and approaches, our work provides a more complete and up-to-date understanding of the challenges and opportunities facing the region as it moves towards a sustainable and globally competitive future. the Peruvian Amazon is seen as a transformative agent with potential that transcends its natural boundaries. By adopting a comprehensive and visionary perspective, the region emerges as a beacon of hope for a sustainable and prosperous future. It is essential that future policies and actions recognize and strengthen these transformative perspectives, ensuring equitable and resilient development that benefits present and future generations. In this way, the Peruvian Amazon not only drives its own global competitiveness, but also inspires and leads the way towards a more prosperous and sustainable world.